Mastitis and death of a Corriedale ewe associated with Mycoplasma spp. infection in Buenos Aires province - Cantón, Germán José (2021)
Mycoplasma spp. infections are associated with different clinical syndromes in ruminants: mastitis, pneumonia, arthritis, otitis, among others. Nevertheless, case reports of clinical diseases associated with Mycoplasma-infections are scarce in small ruminants of Argentina. Mycoplasma agalactiae and Mycoplasma capricolum are the causal agents of contagious agalactia, an exotic disease in the region, although M. agalactiae was detected by PCR. Therefore, strict surveillance of these pathogens is needed. We report a case of severe mastitis and death of a 7-years-old Corriedale ewe in a flock from Buenos Aires province. The affected ewe had delivered twin lambs 15 days before clinical disease was detected and died. During post mortem examination, supramammary lymphadenomegaly was evident. Mammary gland was enlarged and firm, with cyanotic skin and superficial edema; multiple caseous whitish foci were observed in the mammary parenchyma. Similar caseous foci were observed in the caudal-ventral lobes of the right lung.